The Influence of Job Training and Competence on Employe Performance at PT Nion Monita Food Indonesia - Ainun Saadaturoin; Editya Nurdiana (Rescollacom (Research Collaborations Community), 2026)
This study explores how job training and competency impact employee performance at PT Nion Monita Food Indonesia. At PT Nion Monita Food Indonesia, management faces challenges in adjusting to new machine technology and improving training efficacy, resulting in a slow pace of work. If not handled, this condition could jeopardize product quality consistency and the company's viability in a highly competitive market. The study employs a quantitative approach, utilizing Structural Equation Modeling (SEM) and SmartPLS on 109 personnel chosen through Proportionate Stratified Random Sampling. The study found that work training and competency can significantly improve employee performance. Structured skill development programs reduce technical errors, while improving individual competencies builds a responsive and independent workforce. These findings highlight the significance of integrating and adapting capacity development strategies to technology changes for long-term corporate performance stability in competitive markets.